What Makes An Effective Vocational High School Entrepreneurial Leadership? Experience From Indonesia - Cindy Agustin Hanivia Cindy (Program Studi Manajemen Pendidikan, 2024)
The government encourages vocational high schools (SMK) to carry out organizational transformation to become SMKs for Regional Public Service Bodies (SMK-BLUD). Through BLUDs, SMKs that have excellent products can manage finances and production processes more flexibly without violating regulations, so that entrepreneurial leadership effectiveness can be achieved. This study aims to analyze the factors that influence the effectiveness of entrepreneurial leadership in vocational high schools using PLS-SEM analysis. Data was obtained by distributing questionnaires to 180 respondents, including teachers, school principals, and committee members at 23 SMK-BLUDs in East Java and the Special Region of Yogyakarta. It is known that the variables of regulation, teacher support, self-capacity, and infrastructure have a positive and significant influence on the quality of entrepreneurial leadership. In addition, the existence of partnerships for each school indirectly has a positive and significant influence on the quality of entrepreneurial leadership. The results of this model show a predictive relevance (Q2) value of 0.96, meaning that this model has good predictive relevance.